Developing Creative Poster-Based Learning Media for Descriptive Writing: A Research and Development Study - Edward Johannes Tumanggor; Angel May Donna Br Sembiring; Zahwa Nabila Andriza Nst; Anggraini Thesisia Saragih; Khairul Azmi Siagian (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Many senior high school students face significant difficulties in generating ideas, organizing thoughts, and selecting appropriate vocabulary when writing descriptive texts. Traditional teaching methods often limit creativity, making the integration of visual media crucial. Therefore, this study aims to develop creative poster-based learning module for teaching descriptive writing. A Research and Development (R&D) design was employed, adapting the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. However, due to time constraints, this research is strictly limited to the Analysis (Needs Analysis) and the initial Development (Prototype Development) stages. The participants for the needs analysis consisted of 22 senior high school students in Indonesia, selected through purposive sampling. Data were collected using an online needs analysis questionnaire. The findings indicate a strong student preference for visual support, which informed the design and creation of a poster-based learning module prototype intended to help students visualize concepts. The implications suggest that while the prototype aligns with student needs, further research is required to validate and test the product.